Transformasi Digital Ekonomi dalam Mendukung Inklusi Keuangan di Indonesia - Muhammad Fauzan Pratama; Bakhtiar Efendi; Lia Nazliana Nasution (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The digital economy plays an important role in promoting financial inclusion by providing wider, more efficient and affordable access to financial services through technology. The digital economy not only includes internet users and fintech but also places importance on sustainability to increase economic growth and reduce inflation in a country. These principles are the purpose of the research to form a strong basis for building an economic model that not only provides short, medium and long term benefits for the people and country of Indonesia. VAR (Vector Autoregression) in the context of econometric analysis is a statistical method used to model the relationship between several time-series variables in the research conducted. The VAR analysis shows that the VAR estimation results highlight the contribution of digital economy variables in measuring financial inclusion. Economic growth is mainly influenced by economic growth itself and savings, showing a significant impact of economic growth and savings. Internet users in the short term are influenced by internet users themselves but in the medium and long term are influenced by fintech as well as fintech variables. For inflation variables in the short and medium term, inflation itself is influenced and in the long term it is influenced by internet users. In the next variable, namely savings in the short and medium term, the biggest influence is inflation then internet users. IRF analysis reveals the response of variables to change and the importance of response stability in the short, medium and long term. In the digital transformation of the economy, that internet users and fintech are the main pillars in realizing digitalization in building financial inclusion but also have an impact on economic growth, savings and ultimately have an impact on inflation. The digital transformation of the economy has a significant impact on financial inclusion, providing a strong basis for digitized or modern economic policies. VAR analysis in IRF and FEVD tests helps reveal the complex interactions between digital economy variables providing valuable insights for effective and sustainable policy formulation.